COMPARISON OF TRAINING LOAD AND RECOVERY BETWEEN CROSS TRAINING AND JUDO (Fiep Bulletin - online, 2025)
Introduction: In the context of high-performance sports, athletes are constantly seeking to improve their performance, and coaches look for the most effective tests to categorize them. Objective: To evaluate and compare the internal training load (ITL), anaerobic power, and fatigue index in recovery and well-being among Cross Training and Judo athletes. Methodology: Thirty volunteers participated in the study, divided into two groups: 15 Judo athletes and 15 Cross Training athletes. The groups were compared using the RAST test, the Rating of Perceived Exertion (RPE) scale, the Perception of Recovery Scale (PRS), and the Well-being Questionnaire (WBQ). Data were analyzed using the Shapiro-Wilk test, independent t-test, Mann-Whitney test, and Pearson's Chi-square (X2) test, with a significance level of p < 0,05. Results: Performance in the RAST test showed no significant statistical difference between the groups, but there were significant differences in RPE, which directly influenced ITL, and also in WBQ. Conclusion: Cross Training and Judo athletes have similar performances regarding anaerobic power. Cross Training athletes had a higher weekly internal training load, but this difference did not affect the athletes' subjective perception of recovery, which was similar in both groups.
Keywords: Cross training; Judo; RAST test; Subjective perception of effort; Subjective perception of recovery